Efektivitas Penggunaan Teknologi dalam Pendidikan Terhadap Kinerja Akademik - Melanie Surya, Ida Ayu; Moramowati, Ni Luh Ayu (Jayapangus Press, 2023)
The use of technology in education has become an increasingly relevant topic and has gained attention in recent years. With the advancement of information and communication technology, education has undergone significant transformation, enabling the adoption of various technological tools and applications to enhance the effectiveness of learning. This study aims to investigate the impact of technology use in education, the challenges faced, and efforts to overcome these challenges. Through literature review, this research also aims to analyze various technology-supported learning models and how their implementation can enrich students' learning experiences. This study uses a literature review method to gather information from various literature sources related to the use of technology in education. Data are analyzed qualitatively to identify relevant trends, challenges, and solutions in the context of technology use in learning. The use of technology in education has a significant impact on improving the effectiveness of learning and enriching students' learning experiences. However, there are challenges that need to be addressed, such as technology accessibility gaps, the quality of learning content, teacher technology skills, and institutional support. By overcoming these challenges and effectively harnessing the potential of technology, education can continue to evolve towards an inclusive, innovative, and technology-oriented learning environment, thus helping to create a generation better prepared to face future challenges and strengthen the learning foundation for a more advanced society.